Biochemical pathways supporting beta-lactam biosynthesis in the springtail Folsomia candida - Suring, Wouter (Biol Open, 2016)
Recently, an active set of beta-lactam biosynthesis genes was reported in the genome of the arthropod springtail Folsomia candida (Collembola). Evidence was provided that these genes were acquired through horizontal gene transfer. However, successful integration of fungal- or bacterial-derived beta-lactam biosynthesis into the metabolism of an animal requires the beta-lactam precursor L-α-aminoadipic acid and a phosphopantetheinyl transferase for activation of the first enzyme of the pathway, δ-(L-α-aminoadipoyl)-L-cysteinyl-D-valine synthetase (ACVS). In this study, we characterized these supporting pathways and their transcriptional regulation in F. candida. We identified one phosphopantetheinyl transferase and three pathways for L-α-aminoadipic acid production, distinct from the pathways utilized by microorganisms. We found that after heat shock, the phosphopantetheinyl transferase was co-regulated with ACVS, confirming its role in activating ACVS. Two of the three L-α-aminoadipic acid production pathways were downregulated, while PIPOX, an enzyme participating in the pipecolate pathway, was slightly co-regulated with ACVS. This indicates that L-α-aminoadipic acid may not be a limiting factor in beta-lactam biosynthesis in F. candida, in contrast to microorganisms. In conclusion, we show that all components for L-α-aminoadipic acid synthesis are present and transcriptionally active in F. candida. This demonstrates how springtails could have recruited native enzymes to integrate a beta-lactam biosynthesis pathway into their metabolism after horizontal gene transfer.